Agronomic Requirements of Tomatoes and Production Methods in the Red River Delta of Vietnam - Ha, Tuan Minh (Department of Agronomy and Horticulture, IPB University, 2015)
Tomato (Lycopersicon esculentum Mill.) (Solanaceae) is one of the most economically important vegetable crops in the Red River Delta (RRD) of Northern Vietnam. The recent market demands for tomatoes in both domestic and overseas markets have led to an increasing cultivated area for the crop in the RRD. To support growers in producing healthy and quality produce, this paper presents in detail the agronomic requirements of tomatoes regarding temperatures, light, water, suitable soil types and nutrients. Cultivation techniques are discussed to provide a general guide for developing appropriate management strategies, depending on specific soil types, cropping seasons, cultivars and availability of resources. In addition, six major pests have been defined, providing useful information for developing an integrated pest management (IPM) program for tomato production in the region.